Comparative evaluation of hydroxyapatite and nano-bioglass in two forms of conventional micro- and nano-particles in repairing bone defects (an animal study) - Saied Nosouhian; Mohammad Razavi; Nasim Jafari-pozve; Mansour Rismanchian (Wolters Kluwer Medknow Publications, 2015)
Context: Many synthetic bone materials have been introduced for repairing bone defects. Aim: The aim of this study is to comparatively evaluate the efficacy of nano-hydroxyapatite (HA) and nano-bioglass bone materials with their traditional micro counterparts in repairing bone defects. Materials and Methods: In this prospective animal study, four healthy dogs were included. First to fourth premolars were extracted in each quadrant and five cavities in each quadrant were created using trephine. Sixteen cavities in each dog were filled by HA, nano-HA, bioglass, and nano-bioglass and four defects were left as the control group. All defects were covered by a nonrestorable membrane. Dogs were sacrificed after 15, 30, 45, and 60 days sequentially. All 20 samples were extracted by trephine #8 with a sufficient amount of surrounding bone. All specimens were investigated under an optical microscope and the percentage of total regenerated bone, lamellar, and woven bone were evaluated. Statistical Analysis Used: Data analysis was carried out by SPSS Software ver. 15 and Mann-Whitney U-test (α =0.05). Results: After 15 days, the bone formation percentage showed a significant difference between HA and nano-HA and between HA and bioglass (P < 0.001). The nano-HA group showed the highest rate of bone formation after 15 days. Nano-bioglass and bioglass and nano-HA and nano-bioglass groups represented a significant difference and nano-bioglass showed the highest rate of bone formation after 30 days (P = 0.01). After 45 days, the bone formation percentage showed a significant difference between nano-bioglass and bioglass and between nano-HA and nano-bioglass groups (P = 0.01). Conclusions: Nano-HA and nano-bioglass biomaterials showed promising results when compared to conventional micro-particles in the repair of bone defects.